2009
DOI: 10.3324/haematol.2008.002626
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling reveals differences in microenvironment interaction between patients with chronic lymphocytic leukemia expressing high versus low ZAP70 mRNA

Abstract: The online version of this article contains a supplementary appendix.Background Zeta-associated protein 70 (ZAP70) is a widely recognized prognostic factor in chronic lymphocytic leukemia, but mechanisms by which its higher expression leads to a poor outcome must still be fully explained. Design and MethodsIn an attempt to unveil unfavorable cellular properties linked to high ZAP70 expression, we used gene expression profiling to identify genes associated with disparities in B cells from chronic lymphocytic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Low transcript levels of the phosphodiesterase 8A (PDE8A) were associated with poor prognosis in our CLL patients. A similar association was reported by Stamatopoulos et al, 8 who showed that PDE8A was part of a gene signature that distinguishes between ZAP70 positive and ZAP70 negative CLL samples. PDE8A might be connected to the NF-kB signaling pathway, which is frequently activated in lymphoid malignancies.…”
Section: Letters To the Editorsupporting
confidence: 86%
“…Low transcript levels of the phosphodiesterase 8A (PDE8A) were associated with poor prognosis in our CLL patients. A similar association was reported by Stamatopoulos et al, 8 who showed that PDE8A was part of a gene signature that distinguishes between ZAP70 positive and ZAP70 negative CLL samples. PDE8A might be connected to the NF-kB signaling pathway, which is frequently activated in lymphoid malignancies.…”
Section: Letters To the Editorsupporting
confidence: 86%
“…42 CD69 has been shown to be a strong predictor of CLL prognosis and to be upregulated by microenvironmental contact. 5,11 The increase in expression of these markers on CLL cells under shear force implicates the action of shear force in the control of expression of these regulators of CLL cell motility.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this concept, gene expression profiling revealed that increased expression of genes that code for proteins involved in the control of cell movement were correlated with poor prognosis. 11,12 One such protein, CD49d, which interacts with vascular cell adhesion molecule 1 (VCAM-1) on endothelial cells during the process of CLL cell migration, has emerged as an important modulator of the pathology of CLL, as evidenced by the fact that it is an independent prognostic marker in this disease. [13][14][15] Here we describe the development and characterization of a novel circulating model system designed to investigate the interactions of CLL cells and endothelial cells under physiologically relevant shear forces.…”
Section: Cd19mentioning
confidence: 99%
“…30 Cells were pre-incubated alone or with SAHA for 24 h before performing the migration assay. Additional details are provided in the Online Supplementary Appendix.…”
Section: Chemotaxis Assays and In Vitro Migration Assay Of Chronic Lymentioning
confidence: 99%